Gagal Jantung pada Penyakit Jantung Bawaan - Nabila, Nurahma; Putri, Giska Tri (CV. Jasa Sukses Abadi, 2025)
Congenital heart disease (CHD) is one of the most common causes of death due to malformations during the embryonic organogenesis process. The survival rate of patients with this disease has increased due to advancements in therapeutic options. Although the success of surgical and medical management of congenital heart disease (CHD) has been very successful, some patients still have hemodynamic abnormalities that lead to long-term cardiovascular complications. One of the complications that causes death in patients with congenital heart disease (CHD) is heart failure. Heart failure in children with congenital heart disease has a 20-fold risk of death, while heart failure in adults has a 25% incidence in patients with congenital heart disease at the age of 30, and this risk increases with age. Because this condition can cause disorders such as growth and cognitive failure, but can also be associated with circulatory, neurohormonal, and molecular abnormalities. The challenge in addressing the risk of morbidity and mortality is related to the limited knowledge regarding the causes of congenital heart disease (CHD), and current evidence suggests etiologi such as unclear factors, including the environment and lifestyle of parents, as well as genetics passed down to the child. This review discusses the causes, epidemiology, and manifestations of heart failure in children and adults with congenital heart disease. The purpose of this review is to understand the epidemiology, classification, clinical manifestations, pathophysiology, and management of heart failure in patients with congenital heart disease.